2020
DOI: 10.3389/fphar.2020.528400
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Modulates the Inflammatory Profile of Immune Responses and Circulating Endothelial Cells’ (CECs’) Population During Acute Whole Body Gamma Irradiation

Abstract: Wistar rats were whole body irradiated with a single dose of 2 Gy post administration with 10 or 100 mg/kg of resveratrol (RSV) intraperitoneally for 30 days. Rats’ livers were dissected and processed to analyze immune response profiles of Th1, Th2, Th9, Th17, and Th22 by flow cytometry. In addition, peripheral blood samples were collected and circulating endothelial cells (CECs) were counted as an indicator for endothelial damage. Results demonstrated that resveratrol at 100 mg/kg enhanced liver immunological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…On the other side, rats exposed to 2 Gy dose of gamma radiation and supplemented with resveratrol 100 mg/kg of resveratrol (RSV) intraperitoneally for 30 days showed an upregulation of IL-6 produced mainly by Th2 cells in rat liver. (35) In this study, the authors suggested that this increase in IL-6 may be involved in tissue repair and regeneration post-irradiation. In our study, using a lower dose (0.60 mg /day), it was found a strong enhance of IL-6 concentration: 13.50 ± 2.52 pg/mL in the supplemented group versus 6.28 ± 0.43 pg/mL in the control, that must be further investigated.…”
Section: Discussionmentioning
confidence: 76%
“…On the other side, rats exposed to 2 Gy dose of gamma radiation and supplemented with resveratrol 100 mg/kg of resveratrol (RSV) intraperitoneally for 30 days showed an upregulation of IL-6 produced mainly by Th2 cells in rat liver. (35) In this study, the authors suggested that this increase in IL-6 may be involved in tissue repair and regeneration post-irradiation. In our study, using a lower dose (0.60 mg /day), it was found a strong enhance of IL-6 concentration: 13.50 ± 2.52 pg/mL in the supplemented group versus 6.28 ± 0.43 pg/mL in the control, that must be further investigated.…”
Section: Discussionmentioning
confidence: 76%
“…47,48 Furthermore, t-Res improved the regulation of signaling molecule Nrf-2, an important regulator in the antioxidant response pathway. 49 Besides, t-Res possesses anti-inflammatory effects, as shown in the study of Khalil et al 50 via reducing the levels of pro-inflammatory mediators and greatly enhancing the expression level of SIRT-1 signaling pathway, which subsequently modulates p53 and NF-κB signals. 48 Also, t-Res significantly inhibited the SOCS-3.…”
Section: Discussionmentioning
confidence: 95%
“…After irradiation, RSV 10 or 100 mg/kg was intraperitoneally administered for 30 days. The results highlighted that RSV 100 mg/kg modulated the liver inflammatory profile of immune response and circulating endothelial cells (CECs) population during acute whole-body gamma irradiation [186].…”
Section: Immunostimulatory Activitymentioning
confidence: 99%